2023
DOI: 10.1002/ptr.7783
|View full text |Cite
|
Sign up to set email alerts
|

Rose essential oil diminishes dopaminergic neuron degenerations and reduces α‐synuclein aggregation in Caenorhabditis elegans models of Parkinson's disease

Abstract: Parkinson's disease (P.D.) is the second most progressive neurodegenerative disorder in the elderly. Degeneration of dopaminergic (DA) neurons and α-synuclein (α-Syn) accumulated toxicity is the major contributor to this disease. At present, the disease has no effective treatment. Many recent studies focus on identifying novel therapeutics that provide benefits to stop the disease progression in P.D. patients. Screening novel and effective drugs in P.D. animal models is time-and cost-consuming. Rose Essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…These EOs possess anti-Aβ, anti-oxidative, and anti-depression-like properties, demonstrating neuroprotective potential in C. elegans. Moreover, in C. elegans treated with 6-Hydroxydopamine hydrobromide (6-OHDA), a neurotoxin that damages the dopaminergic neurons and is thus considered a PD model, rose EOs reduced α-Syn aggregations and diminished dopamine neuron degenerations, reversing the food-sensing behavioral disabilities induced by the 6-OHDA treatment, and prolonging the lifespan of the nematode [39]. In this study, an increased SOD-3 activity in neurons was also observed, that has been linked to the anti-oxidative effect of rose EO that is indeed capable to reduce internal cellular ROS levels [39].…”
Section: Essential Oils and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These EOs possess anti-Aβ, anti-oxidative, and anti-depression-like properties, demonstrating neuroprotective potential in C. elegans. Moreover, in C. elegans treated with 6-Hydroxydopamine hydrobromide (6-OHDA), a neurotoxin that damages the dopaminergic neurons and is thus considered a PD model, rose EOs reduced α-Syn aggregations and diminished dopamine neuron degenerations, reversing the food-sensing behavioral disabilities induced by the 6-OHDA treatment, and prolonging the lifespan of the nematode [39]. In this study, an increased SOD-3 activity in neurons was also observed, that has been linked to the anti-oxidative effect of rose EO that is indeed capable to reduce internal cellular ROS levels [39].…”
Section: Essential Oils and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Moreover, in C. elegans treated with 6-Hydroxydopamine hydrobromide (6-OHDA), a neurotoxin that damages the dopaminergic neurons and is thus considered a PD model, rose EOs reduced α-Syn aggregations and diminished dopamine neuron degenerations, reversing the food-sensing behavioral disabilities induced by the 6-OHDA treatment, and prolonging the lifespan of the nematode [39]. In this study, an increased SOD-3 activity in neurons was also observed, that has been linked to the anti-oxidative effect of rose EO that is indeed capable to reduce internal cellular ROS levels [39]. The same rose EO was tested in an AD model based on transgenic CL4176 C. elegans which overexpresses the human Aβ1−42 gene when the temperature rises from 15 to 25 • C. In these worms, rose EO significantly inhibited AD-like symptoms, such as worm paralysis and hypersensitivity to exogenous 5-hydroxytryptamine, in a dose-dependent manner.…”
Section: Essential Oils and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Given that PD and related disorders are incurable at present, the utilization of EOs could potentially be used as a complementary therapy for improving patients' quality of life [29], despite the fact that their effectiveness against certain aspects of neurodegenerative diseases (dementia, anxiety and agitation) still remains unclear [30][31][32][33][34]. There is increasing evidence that EOs and their constituents can have an impact against PD due to neuroprotective [35][36][37], antioxidant [35][36][37], antiinflammatory [36], anti-apoptotic [35,36] and proteasome- [35] and autophagy-modulating properties [36,37]. However, our knowledge regarding the effect that EOs or their constituents have on α-syn aggregation is rather limited, and the existing information is contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…However, our knowledge regarding the effect that EOs or their constituents have on α-syn aggregation is rather limited, and the existing information is contradictory. While Myrtus communis (common Myrtle) EO increases the rate of α-syn fibrillation [38], the Rosa Setate x Rosa Rugosa (Kushui rose) EO [35], as well as cuminaldehyde, the main constituent of Cuminum cyminum (cumin) EO [39], has the opposite effect.…”
Section: Introductionmentioning
confidence: 99%